BOOK REVIEW -Computer Application II (Trinity Journal of Management, IT & Media (TJMITM), 2010)
Internet has made our lives simpler by connecting us to  the other parts of the world. World Wide Web, the most  important ingredient has helped not only business  personnel but also individuals in expressing and sharing  their thoughts, ideas, opinions, and facts. It is through the  webpage and its technology that one can display the  products, prices, features or anything either as text or  picture with visual effects, sound and video. This book  therefore attempts to integrate the concepts of World  Wide Web with the methodology of creation of a website.  This book follows the functional approach which is  visible from the example under each heading and sub  heading. In the first unit of the book, concept of web  technology, major characteristics of web, planning your  website topics are fully explained. In concept of web  technology how www(world wide web) works, domain,  IP address, URL (uniform resource locator), internet  protocol, HTTP, SMTP/MIME, web caching, web server,  proxy server, firewall, scripting languages (HTML, XML,  JAVA Scripting), portal, home page, cookies, browsers,  search engine, internet & intranet, extranet are fully  explained basic tools & techniques which are used to  design or to run the website. In major characteristics web  server, web browsers, ISP (Internet Service Provider), IIS  (Internet information service), internet explorer are fully explained. This shows the important characteristics of  web & Internet technology.
Keywords: technology; products; prices; domain; IP address